Right ventricular failure after left ventricular assist device implantation: a review of the literature - Lo Coco, Valeria (J Thorac Dis, 2021)
Right ventricular failure (RVF) following left ventricular assist device (LVAD) implantation remains a major complication which may significantly impair patient outcome. The genesis of RVF is, however, multifactorial, and the mechanisms underlying such a condition have not been fully elucidated, making its prevention challenging and the course not always predictable. Although preoperative risks factors can be associated with RV impairment, the physiologic changes after the LV support, can still hamper the function of the RV. Current medical treatment options are limited and sometimes, patients with a severe post-LVAD RVF may be unresponsive to pharmacological therapy and require more aggressive treatment, such as temporary RV support. We retrieved 11 publications which we assessed and divided in groups based on the RV support [extracorporeal membrane oxygenation (ECMO), right ventricular assist device (RVAD), TandemHeart with ProtekDuo cannula]. The current review comprehensively summarizes the main studies of the literature with particular attention to the RV physiology and its changes after the LVAD implantation, the predictors and prognostic score as well as the different modalities of temporary mechanical cardio-circulatory support, and its effects on patient prognosis for RVF in such a setting. In addition, it provides a decision making of the pre-, intra and post-operative management in high- and moderate- risk patients.